Tailored Treatments in Psoriatic Patients - Aghaei, Shahin (IntechOpen, 2019)
The cause of psoriasis is still unknown, though exposure to definite agents (throat streptococcal infection), smoking, alcohol consumption, certain medicines (lithium), and local irritation or injury to the skin may be risk factors for persons genetically predisposed to the disease. Psoriasis symptoms can vary extensively, from mild rashes to severe situations. Treatment consists of various modalities used locally on the skin and taken by mouth. This book gathers and presents information on targeted treatments for psoriasis in four chapters. Following the Introductory chapter, Chapter 2 discusses evaluation of patients with psoriasis and recommended clinical approaches; Chapter 3 presents the etiology, differential diagnosis, clinical findings, and treatment of nail psoriasis; Chapter 4 updates the clinical knowledge on phototherapy for treating psoriatic lesions of the tongue; and Chapter 5 considers potential adverse skin reactions in psoriatic patients taking TNF alpha inhibitors.